Evaluation of Salmonella detection and enumeration throughout the ground turkey supply chain - Tzirin Patal, Marvin Obed (My University, 2024)
Non-typhoidal Salmonella enterica (hereafter referred to as Salmonella) is a significant foodborne pathogen worldwide and is one of the major causes of diarrheal disease. Salmonellosis, the enteric disease caused by Salmonella, can have fatal effects on people’s health, especially for vulnerable populations. Sources of Salmonella contamination in food have a wide range; however, poultry products (including chicken and turkey) are known to be primary reservoirs. Some of the challenges associated with controlling Salmonella in poultry arise from the complexity of the supply chain and the different sources of Salmonella at each stage within it. Reducing the risk of salmonellosis associated with poultry products, particularly ground turkey, is currently a priority for the United States Department of Agriculture Food Safety and Inspection Services (USDA-FSIS). Therefore, the turkey industry is in need of holistic approaches to reduce Salmonella that consider the sources of contamination along the supply chain and its impact on final product contamination. The objective of this study is to evaluate the Salmonella detection and quantification throughout the turkey supply chain to better understand Salmonella contamination in ground turkey. Thus, sixty-six commercial turkey barns were sampled at four levels of the supply chain (i.e., farm, early harvest, processing, and final product). Various sample types were considered, including boot swabs, feathers, and fan dust swabs at the farm level; trailer swabs, paw swabs, and vent swabs at the early harvest level; and livers, lungs, ceca, and ground turkey at the processing and final product levels. Samples were tested for Salmonella using the BAX® System Real-Time PCR Assay, and those that tested positive were quantified using the BAX System SalQuant® assay. Growers filled out a questionnaire with 15 questions regarding barn management, and 19 health variables were monitored during each barn processing to document risk factors. Overall, Salmonella was found in 21.6% of the samples (812 out of 3,766). The empirical prevalence levels varied across sample types, ranging from 2.9% from ceca to 51.2% from vent swabs. Notably, ground turkey had a contamination rate of 28.2%. Results found significant differences in the probability of Salmonella detection across sample types and sampling locations along the supply chain. Early harvest had the highest estimated probability of detection at 38.9% (95% confidence interval, CI [28.3, 50.6]), while processing had the lowest at 2.4% (95% CI [1.4, 4.1]). The quantification dataset posed a challenge as 44.7% of the observations were below the limit of quantification, likely due to technical limitations of analytic assay. For quantifiable samples, the overall Salmonella level mean was 2.19 log CFU/unit (SD 1.34) with varying levels across sample types. Results showed that Salmonella prevalence fluctuates along the turkey supply chain. These findings provide meaningful insights for the turkey industry to understand better Salmonella dynamics along the supply chain and its impact on the safety of ground turkey.
Keywords: Salmonella; Poultry; Turkey; Food safety; Ground turkey; Supply chain